(untitled) (Delito y Sociedad, 2025)
This article presents an intervention experience focused on psychosocial support and legal counseling for individuals declared not guilty by reason of insanity for mental and sentenced to curative security measures in Uruguay. It identifies difficulties in accessing justice for these individuals, who face the criminal justice system without a support model. Furthermore, the application of these measures entails intervention by the criminal justice system without established time limits, given that the Uruguayan Penal Code of 1933 does not set minimums or maximums for this type of sanctioning response. The article analyzes the regulatory framework and its tensions with human rights, describes partial discharge strategies promoted by psychiatric professionals, and presents the methodology of the intervention project developed between 2022 and 2024, highlighting the main challenges in defending the rights of individuals who have been declared not responsible and sentenced to compulsory security measures by the Uruguayan criminal justice system.